Characterization, Antioxidant and Antibacterial Potentials of Tamarindus indica L. Fruit Pulp Extract Loaded O/W Nanoemulsions - Sarunyoo Songkro; Nadia Isnaini; Supreedee Sungkharak; Niwan Tanmanee; Duangkhae Maneenuan; Nattha Kaewnopparat (Universidade de São Paulo, 2022)
Abstract The main purposes of the current study were to formulate o/w nanoemulsions as a carrier for Tamarindus indica (tamarind) fruit pulp extract and to study the antioxidant and antibacterial potentials of nanoemulsions containing tamarind extract, focusing on cosmetic/hygiene applications. The o/w nanoemulsions using a mixture of Tween 80 and Span 80 as an emulsifier (5%w/w) were prepared by a high pressure homogenization process. Two concentrations of sweet tamarind extract, 3.3 and 6.6%w/w, based on the bioactivity study, were incorporated into the blank nanoemulsions to produce loaded nanoemulsions, F1-3.3TE (3.3%) and F1- 6.6TE (6.6%). As compared with the unloaded nanoemulsion, both tamarind extract loaded nanoemulsions showed reduced pH and significantly increased viscosity. Overall, the loaded nanoemulsions had droplet sizes of approximately 130 nm, zeta potential around -38 mV and polydispersity index (PDI) values less than 0.2. The nanoemulsion F1-3.3TE had better stability (e.g. significantly greater % tartaric acid content and lesser PDI value) than the nanoemulsion F1-6.6TE did. The antioxidant activity using 2,2-diphenyl-1-picrylhydrazyl assay revealed that the nanoemulsions F1-3.3TE and F1-6.6TE had scavenging activities of 81.66 ± 0.77% and 63.80 ± 0.79%, respectively. However, antioxidant activity of these two formulations decreased under stress conditions (heating-cooling cycles). Such incidence did not occur for their antibacterial properties investigated by agar well diffusion technique. The two formulations exhibited inhibition zones of approximately 24.0-27.7 mm against Staphylococcus aureus and Staphylococcus epidermidis, responsible for malodor of underarms. The results suggest the potential of using sweet tamarind pulp extract loaded nanoemulsions as hygiene products.